2020
DOI: 10.21037/gs-20-546
|View full text |Cite
|
Sign up to set email alerts
|

Apparent diffusion coefficient magnetic resonance imaging (ADC-MRI) in the axillary breast cancer lymph node metastasis detection: a narrative review

Abstract: The presence of axillary lymph nodes metastases in breast cancer is the most significant prognostic factor, with a great impact on morbidity, disease-related survival and management of oncological therapies; for this reason, adequate imaging evaluation is strictly necessary. Physical examination is not enough sensitive to assess breast cancer nodal status; axillary ultrasonography (US) is commonly used to detect suspected or occult nodal metastasis, providing exclusively morphological evaluation, with low sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Especially when a suspicious breast cancer is found, it is more valuable to assess whether there is metastasis in the lymphatic drainage areas of the breast, such as the axilla, subclavian, and posterior sternum, which is helpful for the clinical staging of breast cancer and assists early clinical development. Patients' prognoses and survival times can be improved by using the appropriate treatment options [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially when a suspicious breast cancer is found, it is more valuable to assess whether there is metastasis in the lymphatic drainage areas of the breast, such as the axilla, subclavian, and posterior sternum, which is helpful for the clinical staging of breast cancer and assists early clinical development. Patients' prognoses and survival times can be improved by using the appropriate treatment options [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Imaging analysis of breast tumor heterogeneity based on diffusion weighted imaging is currently attracting great attention internationally. Previous studies have found some significant DWI imaging features of breast molecular typing and the relationship between ADC values in tumors and surrounding stromal regions and pathological status [ 24 , 28 ], but ADC values in tumors and surrounding stromal regions were found. The heterogeneous signaling patterns and the use of these features to predict molecular typing have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The apparent diffusion coefficient (ADC) values were measured at the machine's accompanying post-processing workstation. The ADC values were calculated through the specific formula [ 16 ]: ADC = ln(SI1/SI2)/800 in which SI1 and SI2 were signal intensities for b =0 and 800 s/mm 2 . The time-intensity curve (TIC) of these lesions was divided into 3 types [ 17 ]: persistently enhancing, platform, and washout.…”
Section: Methodsmentioning
confidence: 99%
“…It was observed a statistically significant difference between the Apparent Diffusion Coefficient (ADC) values on DWI Imaging of pathological and non-pathological lymph nodes, being lower in the pathological ones. The possible functional mechanism is that high cellularity in lymph node metastases produced by the tumor cells, may decrease extracellular and intracellular spaces, and restrict water molecules’ mobility, finally leading to a reduction in ADC value [ 28 ]. Fardanesh et al have found that the median values of mean ADC, maximum (max) ADC and minimum (min) ADC were significantly lower for malignant lymph nodes rather than benign axillary lymph nodes.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%